Ovine CD14- an Immune Response Gene Has a Role Against Gastrointestinal Nematode Haemonchus contortus—A Novel Report - Rawat, Kavita; Pal, Aruna; Banerjee, Samiddha; Pal, Abantika; Mandal, Subhas Chandra; Batabyal, Subhasis (Frontiers in Immunology, 2021)
CD14 (also known as monocyte differentiation antigen) is an important immune response gene known to be primarily responsible for innate immunity against bacterial pathogen and as pattern recognition receptor (PRR) binds with LPS (endotoxin), lipoproteins, lipotechoic acid of bacteria.So far very limited work has been conducted in parasitic immunology. In the current study, we reported the role of CD14 in parasitic immunology in livestock species (sheep) for the first time. Ovine CD14 is characterized as a horse-shoe shaped as a bent solenoid with a hydrophobic amino-terminal pocket for CD14 along with domains. High mutation frequency was observed, out of total 41 mutations identified, 23 mutations were observed to be thermodynamically unstable and 11 mutations were deleterious in nature, causing major functional alteration of important domains of CD14, an indicative for variations in individual susceptibility for sheeps against Haemonchus contortus infestations. In silico studies with molecular docking reveals a role of immune response against Haemonchus contortus in sheep, which is later confirmed with experimental evidence through differential mRNA expression analysis for sheep, which revealed better expression of CD14 in Haemonchus contortus infected sheep compared to that of healthy sheep. We confirmed the above findings with supportive evidences with haematological and biochemical analyses. Phylogenetic analysis was conducted to assess the evolutionary relationship with respect to human and observed that sheep may well be used as model organism due better genetic closeness compared to that of mouse.